Long-Term Activation of Group I Metabotropic Glutamate Receptors Increases Functional TRPV1-Expressing Neurons in Mouse Dorsal Root Ganglia - Masuoka, Takayoshi; Kudo, Makiko; Yoshida, Junko; Ishibashi, Takaharu; Muramatsu, Ikunobu; Kato, Nobuo; Imaizumi, Noriko; Nishio, Matomo (Frontiers in Cellular Neuroscience, 2016)
Damaged tissues release glutamate and other chemical mediators for several hours. These chemical mediators contribute to modulation of pruritus and pain. Herein, we investigated the effects of long-term activation of excitatory glutamate receptors on functional expression of transient receptor potential vaniloid type 1 (TRPV1) in dorsal root ganglion (DRG) neurons and then on thermal pain behavior. In order to detect the TRPV1-mediated responses in cultured DRG neurons, we monitored intracellular calcium responses to capsaicin, a TRPV1 agonist, with Fura-2. Long-term (4 h) treatment with glutamate receptor agonists (glutamate, quisqualate or DHPG) increased the proportion of neurons responding to capsaicin through activation of metabotropic glutamate receptor mGluR1, and only partially through the activation of mGluR5; engagement of these receptors was evident in neurons responding to allylisothiocyanate (AITC), a transient receptor potential ankyrin type 1 (TRPA1) agonist. Increase in the proportion was suppressed by phospholipase C, protein kinase C, mitogen/extracellular signal-regulated kinase, p38 mitogen-activated protein kinase or transcription inhibitors. Whole-cell recording was performed to record TRPV1-mediated membrane current; TRPV1 current density significantly increased in the AITC-sensitive neurons after the quisqualate treatment. To elucidate the physiological significance of this phenomenon, a hot plate test was performed. Intraplantar injection of quisqualate or DHPG induced heat hyperalgesia that lasted for 4 h post injection. This chronic hyperalgesia was attenuated by treatment with either mGluR1 or mGluR5 antagonists. These results suggest that long-term activation of mGluR1/5 by peripherally released glutamate may increase the number of neurons expressing functional TRPV1 in DRG, which may be strongly associated with chronic hyperalgesia.